The value of intrapartum ultrasound in the prediction of persistent occiput posterior position: Systematic review and meta-analysis. (July 2019) - Tao, Hui; Wang, Rongli; Liu, Weifang; Zhao, Yin; Zou, Li
Abstract: Objective: To determine whether ultrasound-assessed occiput posterior (OP) position during labor can predict OP position at delivery. Study design: We performed a systematic literature search in PubMed, EMBASE and the Cochrane Library from inception to February 2019. Included studies needed to report both the fetal head position in labor, as assessed by ultrasound, and the corresponding actual occiput position at delivery. We used a bivariate mixed-effects model to synthesis data. We also calculated I² to test heterogeneity and explored the source of heterogeneity by meta-regression and subgroup analysis. Results: Sixteen primary articles were included in this meta-analysis. Overall sensitivity and specificity of intrapartum ultrasound for prediction of persistent OP position were 0.85 (95%CI: 0.67 to 0.94) and 0.83 (95%CI: 0.77 to 0.87), respectively. The area under the receiver operating characteristic curve was 0.89 (95%CI: 0.86 to 0.91). Substantial heterogeneity was detected (I² = 98, 95%CI: 97–99), and the labor stage at ultrasound examination may be the source of heterogeneity (P = 0.00). After the stratification by extent of cervical dilatation, the predictive sensitivity and specificity at cervical dilatation ≥4 cm reached 0.92 (95%CI: 0.85 to 0.99) and 0.85 (95%CI: 0.80 to 0.91), respectively. Conclusion: Intrapartum ultrasound is a helpful tool for predicting persistent OP position, but the results of the test, especially the ultrasound examination before or at the beginning of labor, must be interpreted with caution. Re-evaluation at late labor is usually necessary.